An idealized molecular geometry library for refinement of poorly behaved molecular fragments with constraints. (1st April 2014) - Guzei, Ilia A.
<x xml:space="preserve">Abstract</x> An idealized molecular geometry library with 40 geometries of molecules and ions optimized by density functional theory methods has been created. All geometries are accessible through a web site. The library entries are tailored for constrained (also known as rigid body) refinements of problematic small‐molecule structures with the OLEX2 and SHELXL software packages. The library application is demonstrated with the refinement of a Pd complex, trans‐Pd(dimethyl sulfoxide)(OH2)(trifluoroacetate)2, that co‐crystallizes in a 2:1 ratio with a solvent molecule of ethyl acetate disordered over an inversion center. Alternative approaches to constrained refinements are discussed.